2020
DOI: 10.1590/1984-3143-ar2019-0116
|View full text |Cite
|
Sign up to set email alerts
|

A Brazilian pulp and paper mill effluent disrupts energy metabolism in immature rat testis and alters Sertoli cell secretion and mitochondrial activity

Abstract: Our objective was to investigate whether the pulp and paper mill industry effluent could affect the testis and Sertoli cells in a fast exposure period. For this, the present study was carried out in immature rats at 10-day-old. Testis treated in vitro with 4% effluent for 1 h presented changes in energy metabolism in terms of a decrease in lactate content and glucose uptake. Elevation in GSH content, as an antioxidant defense mechanism, was also detected. Sertoli cells treated with 4% effluent for 1 hour showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This study also compared the primary effluent from the same company, concluding that the activated sludge treatment decreased, but did not eliminate these estrogenic effects. In turn, Oliveira et al ( 2020 ) exposed immature rat testis and Sertoli cells to 4% secondary effluent for 1 h, verifying alterations in energy metabolism and mitochondrial activity, respectively. Together, these data show that conventionally treated effluents from Brazilian pulp and paper industries can still contain toxic and estrogenic compounds.…”
Section: Toxicity and Estrogenic Activity In Pulp And Paper Mill Effl...mentioning
confidence: 98%
“…This study also compared the primary effluent from the same company, concluding that the activated sludge treatment decreased, but did not eliminate these estrogenic effects. In turn, Oliveira et al ( 2020 ) exposed immature rat testis and Sertoli cells to 4% secondary effluent for 1 h, verifying alterations in energy metabolism and mitochondrial activity, respectively. Together, these data show that conventionally treated effluents from Brazilian pulp and paper industries can still contain toxic and estrogenic compounds.…”
Section: Toxicity and Estrogenic Activity In Pulp And Paper Mill Effl...mentioning
confidence: 98%
“…Thus, if they are affected in early life, they are likely to remain affected until adulthood ( Sharpe et al, 2003 ). Indeed, altered blood homeostasis due to neonatal hormonal dysregulation in mice ( Sarkar and Singh 2017 ) or early exposure to environmental toxins in rats ( Sadler-Riggleman et al, 2019 ; de Oliveira et al, 2020 ) were shown to alter energy metabolism of Sertoli cells. Exposure to high fat diet and resulting diabetes can also alter both glucose and lipid metabolism of mouse Sertoli cells ( Luo et al, 2020 ), which may contribute to altered reproductive functions in response to diabetes ( Sajadi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly critical in early life, because Sertoli cells lose their mitotic activity during postnatal development and thus, if they are affected in early life, they are likely to remain so until adulthood (Sharpe et al 2003). Indeed, altered blood homeostasis due to neonatal hormonal dysregulation in mice (Sarkar and Singh 2017) or early exposure to environmental toxins in rats (de Oliveira et al 2020; Sadler-Riggleman et al 2019) were shown to alter the energy metabolism of Sertoli cells. Exposure to high fat diet and resulting diabetes can also alter both glucose and lipid metabolism of mouse Sertoli cells (Luo et al 2020), which may contribute to altered reproductive functions in response to diabetes (Sajadi et al 2019).…”
Section: Introductionmentioning
confidence: 99%